Snug in Mama's Arms - Medearis, Angela Shelf 1956-; Sandford, John (Columbus, Ohio : Gingham Dog Press, 2004)
As she snuggles her daughter in her arms at bedtime, a mother describes how animals and children around the world go to sleep.
Keywords: Bedtime -- Fiction; Mother and child -- Fiction; African Americans -- Fiction; Stories in rhyme